Compensating the passengers. A comparison of the management of three London underground crashes 1909–1975. Issue 8 (16th November 2020) - Fowler, James
Abstract: This study considers organisational responses to three accidents on the London Underground 1909–1975. The private sector response to an accident at Moorgate in 1909 made generous awards. Responses to the Charing Cross crash in 1938 during the period of quasi-public governance by the London Passenger Transport Board show ongoing high levels of awards. Finally, a severe accident at Moorgate in 1975 reveals public sector management making low offers of compensation. This is congruent with other examples from the industry in each period. The study finds that the fall in compensation was linked to the roles of competition and media interest.